2017
DOI: 10.1177/2055102917718376
|View full text |Cite|
|
Sign up to set email alerts
|

Stress at work: Factors associated with cognitive disorganisation among private sector professionals

Abstract: This study explores psychological and psychological variables associated with perceived stress at work. A total of 100 international participants consented to donating a hair sample and completing a work-related stress survey. Logistic regression was used to investigate associations with low/high cognitive disorganisation using data collected from hair cortisol analysis and self-report questionnaires. High cognitive disorganisation scores were associated with high cardiopulmonary and anger scores. Low perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Boschi and colleagues found that a relationship between high cognitive disorganisation and high cardiopulmonary and anger scores as well as low perceived selfefficacy was associated with high cognitive disorganisation, suggesting a putative role of thinking patterns and state of mind on visceral factors. In particular, perception of what is stressful may lead to the body's stress activation pathways, which in turn may cause cognitive impairment [36]. Interactions between social and genetic risk factors have been investigated by Hasselgren who found a significant effect of work control on dementia risk only for men, along with a moderation effect of the major genetic risk factor for Alzheimer's disease, that is, apolipoprotein E allele [37].…”
Section: Resultsmentioning
confidence: 99%
“…Boschi and colleagues found that a relationship between high cognitive disorganisation and high cardiopulmonary and anger scores as well as low perceived selfefficacy was associated with high cognitive disorganisation, suggesting a putative role of thinking patterns and state of mind on visceral factors. In particular, perception of what is stressful may lead to the body's stress activation pathways, which in turn may cause cognitive impairment [36]. Interactions between social and genetic risk factors have been investigated by Hasselgren who found a significant effect of work control on dementia risk only for men, along with a moderation effect of the major genetic risk factor for Alzheimer's disease, that is, apolipoprotein E allele [37].…”
Section: Resultsmentioning
confidence: 99%
“…14 This put in perspective importance of adequate managerial support through good quality leadership and improvement of employees' skill discretions (skill developments) to enhance productivity especially in terms of cognitive and time demands. 15,16…”
Section: Discussionmentioning
confidence: 99%
“…EFCvR is supported by a Vidi grant from the Netherlands Organisation for Scientific Research NWO (grant number: 91716453). 65 Gidlow et al 2016 46 ; Van Holland et al 2012 63 Need for recovery Van Holland et al 2012 63 Qi et al 2015 52 Cognitive disorganization Boschi et al 2017 67 Health outcomes…”
Section: Acknowledgmentsmentioning
confidence: 99%